Tunneling Control and Good Corporate Governance to Improve State-Owned Enterprises Performance - Siti Arifah; Rahmawati Rahmawati; Agung Nur Probohudono; Setianingtyas Honggowati; Sri Hartoko; Sri Murni; Kiswanto Kiswanto (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2023)
This research aims to look at the influence of tunneling and GCG variables on the performance of Indonesian State-Owned Enterprises. The data used is secondary data taken from the Annual Report of Indonesian State-Owned Enterprises. The data period is six years, from 2014 to 2019. The population in this study was 44 Indonesian State-Owned Enterprises, and the sample was determined using purposive sampling methods. The data is processed using multiple linear regression analysis. The results of the data analysis showed that tunneling and GCG had a significant effect on the performance of Indonesian State-Owned Enterprises, both simultaneously and partially. This study implies that more technical regulations are needed to regulate the boundaries of related transactions in State-Owned Enterprises so that tunneling actions can be minimized. State-Owned Enterprises must also always improve their performance to be more optimal, at least it can increase of State Owned Enterprises that can deposit dividends into the state treasury. The novelty of this research is the use of SOE objects for tunneling subjects that are generally research in private companies.